Effect of Management Control System on Employee Performance at PT. Sigma Poly Internusa During Covid-19 - Mosa Aprilriyan Tjipta; Maria Natalia (SINTESA, 2022)
The Covid-19 pandemic has a negative impact on a country’s economy. Therefore, every company is required to carry out its business activities in a more professional. In carrying out its business activities, a management control system is needed to be able to regulate and evaluate every company policy in achieving their goals. This study aims to analyze